Violence and Gender in the Globalized World, edited by Sanja Bahun and V.G. Julie Rajan - Duggan, Marian (feminists@law, 2016)
Book review of Sanja Bahun and V.G. Julie Rajan (eds), Violence and Gender in the Globalized World: The Intimate and the Extimate (Ashgate, 2nd ed, 2015).